Contextualising contexts - Scholarship of Teaching and Learning and cultural difference - Peter Looker (University of Johannesburg, 2018)
SOTL has an originary moment and a well-rehearsed history. It has been constructed as an approach to understanding teaching and learning with a focus on reflective practice to improve practice and student learning, but it excludes sociocultural influences. This paper argues that by concentrating on the 'classroom', and cognitive measures of success, SOTL conforms to a Western view of what is valuable in education. This instrumentalist perspective allows the process of SOTL to seem universally applicable. It is argued that this instrumentalist approach is a black-box perspective, analogous to the black box of the mind seen in behaviourism. Using Chakrabarty's notion of "provincializing Europe", some structural elements of SOTL history are analysed with an eye to provincialising SOTL. Following this, a personal teaching experience across two cultures is described to demonstrate the inability of SOTL to comprehend the behaviour of students across different cultures without providing more contextual information. Differences between East Asian and Western views of cognition are presented to suggest that cultural differences in conceptions of learning have a significant effect on what happens in the classroom. In conclusion, if SOTL is to be meaningful internationally, it needs both to embrace and be explicit about sociocultural influences and, crucially, it needs to be decentred from Western hegemonic practice. How to cite this article: LOOKER, Peter. Contextualising contexts - Scholarship of Teaching and Learning and cultural difference. Scholarship of Teaching and Learning in the South, v. 2, n. 1, p. 112-128, Apr. 2018. Available at: http://sotl-south-journal.net/?journal=sotls&page=article&op=view&path%5B%5D=32 This work is licensed under the Creative Commons Attribution 4.0 International License. To view a copy of this license, visit http://creativecommons.org/licenses/by/4.0/